Pengaruh Karakter Profil Pelajar Pancasila Terhadap Hasil Belajar Fisika di SMA Negeri 2 Lubuk Pakam - Juanta, Palma; Sinaga, Elvina; Nainggolan, Gabariel; Gultom, Markus Lambok; Defitra, Niko (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2024)
This research analyzes the influence of the Pancasila Student Profile (P3) character on physics learning outcomes at SMA Negeri 2 Lubuk Pakam. This research used quantitative methods with a questionnaire design and data involving 62 class XI students who were divided into control and experimental groups. Data was collected via questionnaire and analyzed using statistical tests. The research results showed that the average character score of students in the experimental class was 74.48, while in the control class it was 72.19, but this difference was not statistically significant (2-tailed Sig of 0.182 > 0.05). There was no significant difference in physics learning outcomes between the two groups. In conclusion, the learning model in the experimental class does not provide better results than conventional learning. It is recommended to use interactive learning media and consider student character in dividing study groups